PENGARUH MOLASES PADA EKOENZIM DAN FILTRAT CAMPURAN FESES SAPI POTONG DAN JERAMI PADI TERHADAP pH, TOTAL BAL DAN KADAR ALKOHOL - Latifah Putri Hafizah Waluyo; Eulis Tanti Marlina; Yuli Astuti Hidayati (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2024)
The beef cattle sector produces waste in the shape of cattle feces, which has yet to be effectively utilized. The farming sector produces waste in the shape of rice straw, but the processing has not been varied. The making of eco enzymes is one of the new ways to process beef cattle feces and rice straw into more useful. The research sought to examine how adding molasses affects the fermentation process of eco-enzymes derived from beef cattle feces and rice straw filtrate. The eco-enzymes were obtained from solid fermentation and liquid fermentation processes. Solid-state fermentation was conducted over a period of seven days, followed by the extraction procedure. The extracted filtrate was fermented facultatively anaerobic for 21 days. The research uses an experimental approach utilizing a completely randomized design or CRD there are 3 treatments, which is the addition of molasses at a dose of P1 = 2.5%, P2 = 5%, and P3 = 7.5%, each repeated 6 times. Data were processed using the ANOVA test and using Tukey’s test for further analysis.  The results showed that molasses dosing had a significant effect (P<0.05) on reducing the pH value to 3.34 - 3.68, producing total Lactic Acid Bacteria (LAB) 6.76x105 - 14.13x 105 CFU/ml, and alcohol content 6.12 - 13.69%.